2017
DOI: 10.1055/s-0043-102403
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of palliative colonic stenting versus emergency surgery for acute proximal malignant colonic obstruction: a multicenter trial

Abstract: Background and study aims Long-term data are limited regarding clinical outcomes of self-expanding metal stents as an alternative for surgery in the treatment of acute proximal MBO. The aim of this study was to compare the long-term outcomes of stenting to surgery for palliation in patients with incurable obstructive CRC for lesions proximal to the splenic flexure. Patients and methods Retrospective multicenter cohort study of obstructing proximal CRC patients with who underwent insertion of a SEMS (n = 69) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…All 82 patients achieved clinical success and had symptom improvement with stoma creation. The overall surgical complication rate of 35.4% is comparable to that reported by Scheidbach et al 13) , but the 30-day mortality included three patients in the ileostomy group. The three patients were in the terminal stage: one of them had cancer ascites due to recurrence of pancreatic cancer and the others had multiple liver metastases due to recurrence of colon cancer.…”
Section: Discussionsupporting
confidence: 79%
“…All 82 patients achieved clinical success and had symptom improvement with stoma creation. The overall surgical complication rate of 35.4% is comparable to that reported by Scheidbach et al 13) , but the 30-day mortality included three patients in the ileostomy group. The three patients were in the terminal stage: one of them had cancer ascites due to recurrence of pancreatic cancer and the others had multiple liver metastases due to recurrence of colon cancer.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, randomized, wellbalanced trials should be conducted to make meaningful judgments about the role of the stent in prognosis. Second, patients mainly underwent ES and gastrointestinal surgery; however, the doctors were not from the same group, and lack of uniform criteria for treatment decisions may lead to bias in choice [11]. Third, due to the limitation of follow-up time, we could not prove the impact of perineural invasion on the long-term survival of patients.…”
Section: Discussionmentioning
confidence: 98%
“…We defined technical success as good placement and smooth expansion of stents under endoscopy and fluoroscopy. Clinical success was defined as intestinal decompression within 72 h after stent placement, with clinical and imaging evidence [11].…”
Section: Colonoscopic Stenting Proceduresmentioning
confidence: 99%
“…Although the conflicting results, the use of SEMS for palliation is recommended also for proximal obstructions [4]. A recent retrospective multicenter cohort study on palliation in patients affected by obstructing proximal colon cancer [16] showed higher technical and clinical success rates for emergency surgical treatment than SEMS. However, surgery had higher hospital stays and higher rates of early Adverse Events (AEs), so that author concluded that SEMS remains the first therapeutical option in this setting and surgery should be reserved in case of failure of endoscopic treatment.…”
Section: Sems and Palliationmentioning
confidence: 99%